Effect of calcineurin inhibition on phenotypic maturation of dendritic cells in an in-vitro model of invasive aspergillosis in lung transplant recipients. (25th February 2016) - Adlakha, Amit; Armstrong-James, Darius; Lenhard, Boris
Abstract: Background: Invasive aspergillosis in lung transplant recipients on immunosuppression has high morbidity and mortality. The calcineurin inhibitor FK506 inhibits the calcineurin–NFAT (nucleated factor of activated T cells) axis, which impairs the innate response to fungal infection. Immature dendritic cells (DCs) have a crucial immune signalling role by phagocytosing antigen, and then maturing and stimulating the T cell response. We investigated the effect of FK506 on phenotypic maturation of DCs in response to Aspergillus fumigatus infection. Methods: Peripheral blood mononuclear cells from healthy volunteers were negatively isolated by density gradient centrifugation (Ficoll, GE Healthcare, Amersham, UK) and were differentiated into DCs with molgramostim (GM-CSF) and interleukin 4. Day 5 cells were matured with interferon (IFN) γ. Day 7 cells were treated with FK506 or inoculated with swollen conidia of A fumigatus (multiplicity of infection 1:1). Cells were then stained with PE-bound anti-CD83 (a late maturation marker) and PerCP-Cy5.5-bound anti-CD209 (a DC-specific marker) and analysed by imaging flow cytometry (ImageStream, Amnis, Seattle, USA). Statistical analysis was performed with Graphpad Prism (version 6.0). Findings: 5000 cells per condition were analysed. The subset of DCs was identified by gating for CD209 positivity. We demonstrated upregulation of CD83 on the surface of DCs with IFNγ stimulation (26 228 mean fluorescence units [SE 1462] vs 12 534 [799], p<0·0001) A fumigatus infection of unstimulated DCs (29 888 [1393] vs 12 534 [799], p<0·0001), and A fumigatus infection of IFNγ-stimulated DCs (36 778 [1356] vs 26 228 [1462], p<0·0001). CD83 mean fluorescence intensity was reduced with FK506 treatment of IFNγ-stimulated DCs (26 228 [1462] vs 20 219 [846], p=0·0004), A fumigatus -infected unstimulated DCs (29 888 [1393] vs 24 289 [1253], p=0·0028), and A fumigatus -infected, IFN γ-stimulated DCs (36 778 [1356] vs 30 159 [1279], p=0·0004), but unchanged for unstimulated, uninfected DCs (12 534 [799] vs 11 942 [762], p=0·5921). Interpretation: Both A fumigatus infection and IFNγ stimulation promote phenotypic maturation of DCs in vitro, and treatment with FK506 inhibits maturation in this context. These findings suggest that FK506 has an inhibitory effect on innate antigen presentation to T cells and that it might impair the adaptive immune response to invasive aspergillosis in lung transplant recipients. Funding: Medical Research Council Chain-Florey Clinical Research Fellowship.